Serological Characterization of C-type Retroviruses Endogenous to the C57BL/6 Mouse and Isolated in Tumours Induced by Radiation Leukaemia Virus (RadLV-Rs) - Astier, T.; Guillemain, B.; Laigret, F.; Mamoun, R.; Duplan, J. F. (Journal of General Virology, 1982)
SUMMARY Radiation leukaemia virus, Rs strain (RadLV-Rs), is a virus complex derived from radiation-induced lymphoma of the C57BL/6 mouse. Several B-ecotropic retroviruses (T1223/B, T98/B and T128/B) were isolated from the RadLV-Rs and further cloned. They were found to be highly leukaemogenic and polymorphic in terms of XC cell fusion activity. To investigate a possible relationship between their phenotypical and genotypical properties, a serological characterization of their proteins was undertaken by means of interference, neutralization and type-specific radioimmunological experiments. In addition, these viruses were compared on the basis of the electrophoretic mobility of their proteins. They were also compared with the prototype endogenous N-ecotropic (BL6/NÌ) and xenotropic (T530/X) retroviruses of the C57BL/6 mouse as well as the AKR-MuLV and the RadLV/VL-3 (thymotropic leukaemogenic retrovirus involved in radio-induced lymphoma). With respect to the pl2, T1223/B and T128/B viruses were of xenotropic type as in RadLV/VL-3, whereas T98/B p12 displayed ecotropic and xenotropic type-specific antigenic determinants. The gp71 of all B-ecotropic virus isolates were indistinguishable and of the AKR-MuLV type. This latter result was further supported by interference and neutralization experiments. This supports the view that the B-ecotropic virus isolates originated by recombination (one or two events) between N-ecotropic and xenotropic endogenous retroviruses. The RadLV/ VL-3 possesses a unique envelope recombinant glycoprotein of which the antigenicity was not observed in the RadLV-Rs complex. Thus, it may be assumed that the leukaemogenic components of RadLV and RadLV-Rs arose by different recombinational mechanisms.
Keywords: C57BL